Nurses' Quality of Work Life - Suaib Suaib; Syahrul Syahrul; Takdir Tahir (State Islamic University of Sunan Ampel, 2019)
The nurse is a professional who has the ability, responsibility, and authority incarrying out nursing services/care at various levels of nursing services whose lives are fully influenced by the quality of work life (QWL) as a consequence of a dynamic change in the work environment. Therefore in order to increase the capacity of nurses in meeting the quality of health services, it is necessary to research the Quality of Work Life. The purpose of the literature study was to identify the nurses’ quality of work life in supporting the improvement of the quality of health services. The database used in the making of this literature review is Pubmed, Science Diret, and Google Scholar published in 2012-2018. There are 6 articles that meet the criteria with the results showing that the fulfillment of QWL nurses can affect organizational commitment, job satisfaction, and turnover. Fulfillment of nurses’ QWL is important to do, where if the nurses’ QWL is fulfilled, it provides many benefits to the nurse and has a direct impact on the health services provided so that organizational attention is needed because QWL is seen as capable of increasing the participation of workers in the organization. The increase in QWL in the hospital can improve the professionalism of nurses and influence the effectiveness and organization productivity.